Voluntary disclosure in Malaysian corporate annual reports: views of stakeholders - Mohd Ghazali, Nazli Anum (Emerald Group Publishing Limited, 2008)
Purpose – The purpose of this paper is to identify ‘‘qualitative’’ factors inﬂuencing voluntary information disclosure in annual reports. Design/methodology/approach – Semi-structured interviews were held with twenty-seven market participants in Malaysia to elicit opinions on issues related to voluntary information disclosure. Findings – Analysis of interview responses revealed that factors inﬂuencing voluntary disclosure in annual reports include the quality of management, gaining analyst trust and promoting company shares, good news versus bad news, the existence of other channel of communication, governance structure and market forces. Research limitations/implications – Some of the ‘‘qualitative’’ factors identiﬁed do not appear to be totally independent from one another. Further work using factor analysis can be an avenue for future research on accounting disclosure. Practical implications – The results also suggest that some companies may be willing to share information to selected interested parties such as analysts during private meetings rather than in a public document such as the annual report. Thus disclosure in a corporate annual report should not be taken as a conclusive measure of a company’s extent of voluntary reporting. Originality/value – This paper is one of few studies which adopts an interview approach to identify ‘‘qualitative’’ factors inﬂuencing voluntary information disclosure in annual reports.